Technologies for the obtaining of sodium chloride (NACL) pharmaceutical degree (Agroindustria, Sociedad y Ambiente, 2019)
The sodium chloride (NaCl) pharmaceutical grade, is a salt that has a particularly high quality and high purity (99.8%), is involved in the elaboration of multiple products in the pharmaceutical and food industry, considered as an essential raw material for the daily life of the human being. The main objective of the research was to identify the most optimal technologies for obtaining. The methodology used was through the use of keywords for the construction of patent search strategies, using platforms such as The Lens, Web of Science and Carrot2; obtaining bibliometric and patentedometric indicators. Among the results obtained suggest that the high vacuum evaporation technique has the greatest application for the purification of sodium chloride due to its high purity, low operational consumption, lower environmental impact and high yields. Currently, many countries have focused on developing technology to obtain higher yields and greater benefits from other products present. It should be noted that Venezuela has natural sources of the mineral, therefore it is necessary to promote the production of sodium chloride as a raw material in different sectors such as pharmaceutical and industrial.
Keywords: Sodium chloride; purification technologies; raw material; USP grade; patents